Tracing the Heroic Through Gender - Mommertz, Monika (Helden - Heroisierungen - Heroismen, 2018)
In nearly all societies and epochs, the heroic is gendered on many levels. However, social and cultural production of the heroic cannot be understood solely through the lens of masculinity, nor does it make sense to regard women or femininity merely as exceptions. Rather, it is important to take the relational character seriously. This volume is the first attempt to employ gender as an analytical category for heroism research. Using diverse approaches from the humanities, gender serves as a tracer of the heroic and as an instrument for examining its historical contexts, its medial and performative manifestations, as well as its temporal cycles and transformations. With the help of the gender category and its attributes, the heroic is reevaluated.